2015
DOI: 10.1021/acs.nanolett.5b03271
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Quantum Dot Photovoltaics Enhanced by Perovskite Shelling

Abstract: Solution-processed quantum dots are a promising material for large-scale, low-cost solar cell applications. New device architectures and improved passivation have been instrumental in increasing the performance of quantum dot photovoltaic devices. Here we report photovoltaic devices based on inks of quantum dot on which we grow thin perovskite shells in solid-state films. Passivation using the perovskite was achieved using a facile solution ligand exchange followed by postannealing. The resulting hybrid nanost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
242
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(262 citation statements)
references
References 41 publications
11
242
2
3
Order By: Relevance
“…To achieve this, we improved upon an anti-solvent phase-boundary exchange method used for 1.3 eV CQDs. 7,8 In this process, oleic-acid (OA)-capped PbS CQDs (OA-PbS) dispersed in octane are mixed with halide precursors that are dissolved in N,Ndimethylformamide (DMF). Previous work on anti-solvent phase boundary exchanges had used methylammonium iodide 7 and methylammonium lead tri-iodide for the ligandexchange process.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve this, we improved upon an anti-solvent phase-boundary exchange method used for 1.3 eV CQDs. 7,8 In this process, oleic-acid (OA)-capped PbS CQDs (OA-PbS) dispersed in octane are mixed with halide precursors that are dissolved in N,Ndimethylformamide (DMF). Previous work on anti-solvent phase boundary exchanges had used methylammonium iodide 7 and methylammonium lead tri-iodide for the ligandexchange process.…”
mentioning
confidence: 99%
“…Previous work on anti-solvent phase boundary exchanges had used methylammonium iodide 7 and methylammonium lead tri-iodide for the ligandexchange process. 8 Here, we use lead iodide (PbI 2 ) that can also act as a ligand, which has recently been shown to increase short-circuit current in a solid-state treatment. 9 Further, the iodide ligands have been demonstrated to be stable under air storage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3c and Table 1, among the devices with active layer numbers of 3, 5, 7, and 10, respectively, the five‐layer device exhibits an optimum PCE of 4.25% with a J sc of 24.83 mA cm −2 , an open‐circuit voltage ( V oc ) of 0.45 V, and a fill factor (FF) of 38%. Note that this PCE is significantly higher than those reported values of traditional EDT‐capped PbS solar cells (≈3%) 7, 8, 24, 25. It is also notably higher than those of EDT capped PbS/CH 3 NH 3 PbI 3 core/shell QDs sensitized solar cells (3.2%)30 and CH 3 NH 3 PbI 3 /oleic acid capped PbS bilayer heterojunction photovoltaic cells (3.6%),31 respectively.…”
Section: Figurementioning
confidence: 55%
“…Recent studies showed an effective strategy of improving FF and PCE in the PbS CQD solar cells by inserting a thin top layer of PbS−EDT 24. We therefore added two layers of p‐type PbS−EDT CQDs (≈50 nm)24 onto the optimal five layers of n‐type PbS−CH 3 NH 3 PbI 3 CQDs (≈300 nm) in solar cells to create graded band structures.…”
Section: Figurementioning
confidence: 99%